Pontos quânticos de carbono incorporados em matriz polimérica para aplicação em diodo emissor de luz - Pontes, Sheyliane Maria Adriano (2022)
The worldwide technological advance drives the search for innovative optoelectronic devices. In this perspective, nanomaterials such as Carbon Quantum Dots (CQD) show promise for replacing inorganic Quantum Dots (QD) used in Light Emitting Diodes of digital displays. The CQD have exceptional properties such as photoluminescence, biocompatibility, synthetic and structural versatility. Thus, this work presents the synthesis and characterization of Multicolor Carbon Quantum Dots (MCQD) incorporated in a polymer matrix to assemble a White Light Emitting Diode (WLED). For this purpose, an optimization of the experimental conditions to obtain MCQD was carried out and its optical and structural properties were evaluated. A solvothermal synthesis using dimethylformamide, citric acid and urea under 166 °C and 11 h and 24 min was selected as optimal conditions from absorption spectral data in the Ultraviolet-visible region. Fluorescence indicated emission throughout the visible region of the electromagnetic spectrum, under excitation source of 380 nm and concentration of 0.22 mg mL-1. It was also verified the formation of aggregated and isolated nanoparticles, with dimensions from 4 to 12 nm and different functional chemical groups in their structure. The MCQD were incorporated in a polymeric matrix (PVA) which resulted in a better color quality than the analyzed commercial WLED, indicated by the Color Rendering Index (CRI). It appears that MCQD have the potential for incorporation in a solid matrix, as well as its application in light emitting diode for the improvement of optoelectronic devices.